Risk assessment in target market selection by bread baking enterprises - Skopenko, Natalia; Fedulova, Irina; Mostenska, Tatyana; Yevsieieva-Severyna, Iryna; Kapinus, Larisa (My University, 2024)
The aim of research is to justify a comprehensive approach to enterprise risk management, which includes analysis of risk factors at the stages of target market selection by enterprise.
Keywords: кафедра маркетингу; кафедра економіки праці та менеджменту; оцінка ризиків; risk assessment; управління ризиками; risk management; ринок хлібобулочних виробів